Lending and credit administration - Sadiku, Babatunde Muhammed Tajudeen (Abuja: Damat - Mega Consult Ltd, 2020)
The book is made up of twenty seven chapters which has practice questions that were used to illustrate and explain the principles behind each topic.
Includes bibliographical references
ucj 07/7/2021
Loans
Keywords: Money; Bank lending; Credit Administration